The effect of FDI on local suppliers: Evidence from Audi in Hungary - Márta Bisztray (Hungarian Academy of Sciences, Institute of Economics, 2016)
In 1993 Audi opened a new plant in Hungary. This paper examines the long-term effects of this large foreign direct investment on local firms operating in supplier industries. I use firmlevel panel data with long time series. Using the method of triple difference-in-differences I compare outcomes of firms in supplier and control industries, close and far from the Audi plant, before and after the entry. My main findings are: (1) after the Audi entry the average annual growth rate of local firms increased by 3 percentage points for sales and 2 percentage points for employment. The effect is visible only five years after the entry of Audi. I find no positive effect on productivity. (2) Firms with foreign owners account for all the positive effect on sales and employment, suggesting a foreign-to-foreign complementarity in investments. Firms with higher productivity gained more. Consequently, the low initial productivity of domestic firms may explain the lack of an effect in this group. (3) New entrants in the supplier industry locating close to Audi are larger and grow faster, suggesting that Audi also had an effect on the extensive margin.
Keywords: F23; R12; 330; foreign direct investment; vertical spillovers; agglomeration